1998
DOI: 10.1074/jbc.273.33.21091
|View full text |Cite
|
Sign up to set email alerts
|

GTP Cyclohydrolase I Inhibition by the Prototypic Inhibitor 2,4-Diamino-6-Hydroxypyrimidine

Abstract: 2,4-Diamino-6-hydroxypyrimidine (DAHP) is considered to be a selective and direct-acting inhibitor of GTP cyclohydrolase I (GTPCH), the first and rate-limiting enzyme in the pathway for synthesis of tetrahydrobiopterin (BH4). Accordingly, DAHP has been widely employed to distinguish whether de novo BH4 synthesis is required in a given biological system. Although it has been assumed that DAHP inhibits GTPCH by direct competition with substrate GTP, this has never been formally demonstrated. In view of apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 22 publications
3
28
1
Order By: Relevance
“…4) (39). In the absence of DAHP, the K m and V max for GTP utilization were 75.52 Ϯ 9.78 M and 46.31 Ϯ 1.23 nmol H 2 NTP/min/mg protein, respectively, in accord with published values (39,43,44). On addition of DAHP, the K m for GTP was modestly increased (100.70 Ϯ 17.34 M), and V max was unchanged (47.48 Ϯ 1.89 nmol H 2 NTP/min/mg protein) as determined by nonlinear regression analysis.…”
Section: Development Of a Novel Kinetic Microplate Assay For Gtpchsupporting
confidence: 77%
See 4 more Smart Citations
“…4) (39). In the absence of DAHP, the K m and V max for GTP utilization were 75.52 Ϯ 9.78 M and 46.31 Ϯ 1.23 nmol H 2 NTP/min/mg protein, respectively, in accord with published values (39,43,44). On addition of DAHP, the K m for GTP was modestly increased (100.70 Ϯ 17.34 M), and V max was unchanged (47.48 Ϯ 1.89 nmol H 2 NTP/min/mg protein) as determined by nonlinear regression analysis.…”
Section: Development Of a Novel Kinetic Microplate Assay For Gtpchsupporting
confidence: 77%
“…L-Phe reverses this inhibition without disrupting the inhibitory complex. The apparent structural similarity of DAHP and BH4 as well as results from previous studies conducted in rat aortic smooth muscle cells (39) and in vitro (45) suggested a possible role for GFRP in the mechanism of DAHP-mediated inhibition. Based on careful analyses using pure recombinant proteins, our findings confirm that a major mode of DAHP inhibition of GTPCH is indeed dependent on GFRP.…”
Section: Figmentioning
confidence: 73%
See 3 more Smart Citations